Knowledge, Risk Perceptions and Preventive Behaviors Regarding to COVID-19 Pandemic in General Population of Sindh, Pakistan - Yasir Akbar Jamali, Saman Soomro, Ashok Kumar, Paras Soomro, Hanozia Shah, Shakil Ahmed, Ali Bux Khuhro (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of this research was to evaluate how Pakistanis feel about and understand COVID-19 Methods: To conduct the cross-sectional survey, we used Google forms to digitize a questionnaire with 17 items, which we then sent to a sample of the general population. Results: There was a total of 615 questionnaires collected from residents of Sindh Province. Most people 75.1% believe that the disease is spread through direct contact with an infected person or through inhaling air droplets expelled by a sick person while they sneeze or cough. When asked how they had avoided contracting COVID-19 over the preceding 14 days, the vast majority, 39.4%, reported consistently washing and sanitizing their hands. Other steps include not shaking hands with people 33.0% and staying at least one meter away from them (24.9%), not letting people share utensils at meals 38.1%, and masking their faces even when they don’t feel sick 28.8%. Additionally, 56.1% of the respondents admitted that they had not taken any special precautions to protect themselves. It is duty of every citizen to obey the government’s steps to avoid from COVID-19. Conclusion: In general, the people who took part knew a lot about the disease and felt good about taking precautions. The government and the public are taking effective steps to stop the spread of disease, but there is still a need for more awareness campaigns and knowledge of safe ways to stop the spread of disease. Keywords: SARS-Cov-2, COVID-19, Sindh, pandemic, epidemic